Violencia física y emocional en el grupo de Adultos Mayores Jesucristo Redentor, San Pedro de Huaca – Carchi. - Chamorro Bastidas, Jhon Jairo (2024)
The objective of this research was to develop an educational plan addressed to preventing emotional and physical violence in elderly people from the group “Jesucristo Redentor” located in San Pedro de Huaca, to diminish the rate of physical and emotional violence in this population. The methodology of this study was framed under the quantitative paradigm which led to a systemic and objective approximation towards the research phenomenon. The type of research was descriptive given its approach in the characterization, detailed and systematic, of the emotional and physical violence. Additionally, bibliographic research was applied, thus analyzing the existing literatura regarding the study research. The method used was analytic-synthetic, integrating diverse perspectives, as to say, theoretical and practical. The population of the study was comprised of 60 elderly people who are part of the group Jesucristo Redentor located in San Pedro de Huaca Canton. The survey was the main technique applied in this research to gather information and the instrument was a structured questionnaire. The most relevant results showed that 64% represent a female population, and 64 % are constantly exposed to physical violence which denotes an imminent risk to their physical and emotional well-being. In addition, it was found that 76% have experienced a high level of loneliness, 64% of the elderly people do not receive any support or assessment to fase physical or emotional violence. Consequently, the development of an educational plan is an effective strategy to inform and educate positively the elders, and thus be a potential factor to diminish the rates of violence among this vulnerable population. The analysis of the current situation exposed a perspective that demands attention, given that it was possible to identify the prevalence of mistreating situations, as well as the diverse factors that contribute to this situation.